Differential protein expression focusing on the mannose phosphotransferase system, in Listeria monocytogenes strains with class 11a bacteriocin resistance - Ramnath, Manilduth (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.